MARKETING MIX STRATEGY OF CALLIGRAPHY, PAINTING, FRAME MSMEs Mr. IDRIS, BULAK KLENDER - Ahmad Rojikun; Agustinus Yanuar Budhi Heriyanto; Evi Noviaty (Asosiasi Dosen Muda Indonesia, 2022)
The potential of productive small industries is small industries that are mainly engaged in souvenirs/handicrafts. MSMEs that have a large role in exports are MSMEs that rely on handmade skills, such as jewelry crafts, wood carvings and including Calligraphic Pigura Crafts. In the process of determining the quality of raw materials directly handled by themselves based on their own experience, but still need to be improved in maintaining the quality of materials, because of the impact on the quality of the final result. The results of observations at calligraphy MSMEs, explained that to ensure the quality of the products produced, MSMEs have based on a sense of trust with parabuyer, meaning that consumers have trusted the quality of the products produced by calligraphy MSMEs,The partner in this activity is Mr. Idris' Calligraphy, Painting and Frame UMKM. The partner's problems are: (1) Lack of promotion, especially utilizing free promotion on social media. (2) Lack of capital, so the products are not many. (3) Inadequate space, utilizing the front yard of the house. (4) There is no logo as the identity of Mr. Idris' MSME business, (5) Products are made by Mr. Idris himself from raw materials to finished products. (6) Lack of information on the tastes of today's consumers, so that the products produced are not sold out quickly. This community service activity offers a solution. The first solution provides an explanation of knowledge to Mr. Idris about the marketing promotion mix that can increase sales results by counseling. The second solution provides an explanation of examples of the marketing mix as reference material, so that it is easily understood with casual conversation. The third solution is to collaborate with Calligraphy, Painting, and Frame MSMEs that have developed, so as to increase the knowledge and development of Mr. Idris' MSME business.